P319 The unexpected 'troublemaker' – Behavioural changes in children with cow's milk protein allergy. (June 2019) - Lendvai-Emmert, Dominika; Emmert, Vanessza; Fusz, Katalin; Prémusz, Viktória; Tóth, Gergely
Abstract : Introduction: The most common food allergy in children is cow's milk protein allergy, and the clinical manifestations of the entity are very diverse. Beside the organic symptoms of milk protein allergy, behavioural problems often occur in these children: the parents describe problems with attention, increased impulsivity and sleeping disorder; the biological background of these symptoms in not fully understood at the moment. The aim of our human research is to examine the psychological aspects induced by these proteins. Methods: Participants of the study were children above 3 years of age, with suggested symptoms of cow's milk protein allergy (n=43). The location of the study was the Paediatric Gastroenterology Department of the Balassa János County Teaching Hospital. The parents of the involved children were asked to fill in a self-edited questionnaire, which contained questions about sociodemographical and health status, as well as features about behaviour (according to DSM-5 symptoms-cheklist about attention deficit-hyperactivity disorder). The evaluation of the questionnaires were performed with SPSS statistical program. Results: Examining the entire research population (n=43, mean age:7.88 years, 41.9% female) the score received according to the ADHD symptoms-cheklist before the diet (6.88, SD: 4.43) showed significant decrease after 3 months of the elimination diet (4.48, SD: 3.69, p=0.001). The above mentioned score of the children with sleeping disorder (n=13, 10.62, SD: 4.23) also represented a significant reduction after 3 months of the diet (6.69, SD: 4.59, p=0.009). Discussion: According to our results it is found that psychological symptoms (attention deficit, hyperactivity, sleeping disorder) can be induced by cow's milk protein allergy, but a significant improvement in these symptoms – beside the somatic symptoms - can only be achieved with a strict elimination diet.